Natural language understanding and cognitive robotics - Yokota, Masao, 1954- (2019)
"Describes the method for robots to acquire human-like traits of natural language understanding (NLU), the core of which is mental image directed semantic theory (MIDST). It is based on the hypothesis that NLU by humans is essentially processing of mental image associated with natural language expressions. MIDST is intended to model omnisensory mental image in humans and provide a knowledge representation system for integrative management of knowledge subjective to cognitive mechanisms of intelligent entities, e.g. humans and robots, with a systematic scheme for symbol-grounding. The book is aimed at researchers and students interested in artificial intelligence, robotics, or cognitive science. Based on philosophical considerations, this will also have an appeal in linguistics, psychology, ontology, geography, and cartography"--
Natural language processing viewed from semantics -- Fundamentals for robotic natural language understanding -- Cognitive essentials for mental image directed semantic theory -- Computational model of mental image -- Formal system -- Fundamental postulates and inference rules for deductive system -- Human-specific semantics of 4D language as mental images -- Problem finding and solving in formal system -- Human language understanding by robots -- 4D language understanding for cognitive robotics -- Multilingual operation via mental image description language -- Computational model of Japanese for natural language understanding -- Implementation of mental-image based understanding -- Robotic imitation guided by natural language.
Includes bibliographical references and index.
Keywords: Natural language processing (Computer science); Human-machine systems; Machine learning; Autonomous robots; Computational intelligence